Neuere Entwicklungen im japanischen Verbraucherrecht - Nakata, Kunihiro (Zeitschrift für Japanisches Recht, 2009)
Regulation of consumer protection in Japan is at present subject to far-reaching changes. Whereas traditionally the policy focus was on promotion of industry and economic growth, increasingly the interests of the consumers are taking over the regulatory stage. In 2008 the Japanese government decided to create a specific public institution in charge of defending consumer interests. Furthermore, various legislative reforms have strengthened the rights of consumers versus industry. This was mainly achieved by creating new civil rights that allow for and make it easier for consumers to fight for their rights in court. This can be characterized as a change from an ex ante regulation by administrative law controlling access to the market to an ex post regulation by granting individual and enforceable rights. Also, information duties of producers were increased. In sum, the Japanese legislator acknowledges the autonomy of consumers. (The editors)